Quantitative Research: Data Collection and Data Analysis for Beginner Researcher in Discussion - Herwanis, Delfia; Alianur, Mudfar; Maulida; Nasir, Khairun (Yayasan Cendekia Gagayunan Indonesia, 2025)
This article is a comprehensive summary of the fundamental components of quantitative research design, specifically designed to cater to researchers who are new to the field. Quantitative research is a methodical and structured technique of investigation that utilizes numerical data and statistical analysis in order to address research inquiries and evaluate hypotheses. Although it may appear intimidating to individuals who are new to the field, this summary provides an overview of the essential stages and factors necessary to commence a profitable quantitative research endeavor. The writing commences by highlighting the significance of a precisely formulated research inquiry and hypothesis, underscoring the necessity for lucidity and precision. This emphasizes the relevance of doing a comprehensive literature evaluation to inform the design of the study and the value of choosing a suitable research methodology. For those who are new to the field, this frequently entails the utilization of surveys, experiments, or the examination of pre-existing datasets. The subsequent section delineates the essential components of study design, encompassing the formulation of a research plan, the creation of data gathering tools, and the utilization of sampling methodologies. The importance of ethical issues and the acquisition of informed permission from participants is underscored. The significance of conducting pilot tests on the research instruments to establish their validity and reliability is also emphasized in the research or study. In conclusion, this writing offers novice researchers a succinct outline of the fundamental elements comprising quantitative research design. This resource provides a valuable foundation for individuals initiating quantitative research endeavors, providing assistance in navigating the essential stages and factors involved in undertaking substantial and methodical research.